Knowledge and Practices Relating To Domestic Accident among Mothers of Pre-School Children in Ibadan Southwest Local Government Area, Nigeria (2013)
The study assessed the knowledge and practices for domestic accident among 756 mothers of preschool children in Ibadan Southwest Local Government Area, Nigeria. Pretested questionnaire with a 15-point knowledge scale relating to domestic accident prevention was used for data collection. Descriptive statistics and ANOVA were used for data analysis. Mean age of respondents was 28.7±5.8 years and 97.8% had at least primary school education. About 30.3% of mothers place cooking utensils on the floor and 46.0% reported domestic accidents [falls (47.0%), burns (23.5%) and ingestion of kerosene (8.4%)] in their preschool children. Domestic accidents were perceived as not totally preventable (85.3%) and part of children’s development (50.8%). Preventive practices employed included consistent monitoring of preschool children (58.5) and keeping drugs in secured boxes (55.5%). Self responsibility (58.1%), perceived danger (37.0%) and fear of husband’s reaction (32.7%) were main influences for adoption of the preventive behaviour. Although knowledge on the causes and prevention of domestic accidents was high among the respondents, preventive practices need to be strengthened. Educational interventions such as training and public enlightenment aimed at empowering mothers and significant others to be more involved in the prevention of domestic accidents among their preschool children are recommended.